From shop houses to shop offices: evolution of modern shop offices design in Malaysia - Awang, Arita Hanim; Denan, Zuraini (WMIT Group Sdn. Bhd, 2017)
Malaysia is approaching its Vision 2020. Kuala Lumpur as the capital city of Malaysia is blooming with development of new commercial and residential buildings. The major components of commercial floor space in Kuala Lumpur are offices, shopping, hotels, service apartments and other services. Office is still the highest services targeted to the strategic zone in Kuala Lumpur and its conurbation. Among the types of office building in Malaysia, shop offices stayed dominant demand for small and medium (SME) business activities. Shop offices type of building is a prominent landscape of business zone in Malaysia especially in Kuala Lumpur emerging conurbations. With the emerging of new office building as well as purposed-built offices, this type of building typology needs to be reviewed and studied. Therefore, this research will be focusing on the office interior condition in shop offices building typology in Kuala Lumpur. Research on office environment and condition in Malaysia are now rising but only in the commercial office building and up until to this date, there is still no research on the office condition in shop office typology especially in the scope of interior design. There are very limited literatures about modern shop offices design available; therefore, the main objective of this study is to review and to record the evolution of modern shop offices in Malaysia. Data was collected through a primary and secondary data collections of various sources namely from site survey, site visits, observations and literature review. The scope of this reseach is limited to shop offices building typology in Kuala Lumpur only. This study is expected to give a better understanding of the modern shop office design and issues that can be further explored in the future.